Short-term prospective clinical evaluation of monolithic and partially veneered zirconia single crowns - Bömicke, Wolfgang; Rammelsberg, Peter; Stober, Thomas (Journal of esthetic and restorative dentistry, 2017)
Objectives The purpose of this study was to prospectively evaluate the short-term clinical performance and esthetics of monolithic and partially (i.e., facially) veneered zirconia single crowns (MZC and PZC, respectively). Methods Between September 2011 and June 2013, 68 participants received 90 MZCs and 72 PZCs. Clinical study documentation was performed at crown cementation (baseline), at the 6-month follow-up, and then yearly thereafter using standardized report forms. Eight participants with 14 single crowns (eight MZCs and six PZCs) dropped out during clinical follow-up. Thus, 60 participants (28 male, mean age 62.5 ± 13.1 years) fitted with 82 MZCs and 66 PZCs were analyzed in February 2016 (Kaplan-Meier survival; mean observation time for the restorations 35.1 ± 6.3 months). Descriptive statistics were calculated for participants' and dentists' esthetic ratings on a numerical rating scale from 0 to 10 (0 = unacceptable color and shape; 10 = excellent color and shape). Results Complications were predominantly biological in nature. One PZC was affected by minor chipping. Cumulative 3-year failure-free survival was 98.5% (standard error (SE), 1.5%) for both MZCs and PZCs. Three-year cumulative complication-free survival (success) was 93.6% (SE 2.8%) for MZCs and 95.5% (SE 2.6%) for PZCs. Three-year cumulative fracture-free survival was 100% for MZCs and 98.5% (SE 1.5%) for PZCs. Crowns of both types were awarded high esthetic scores by participants and dentists. Conclusions Monolithic and partially veneered zirconia crowns can be used clinically with excellent short-term survival and success and without compromising esthetic appearance. Longer-term follow-up is, however, desirable. Clinical Significance During the observation time, both monolithic and partially veneered zirconia crowns showed an outstanding low technical complication rate: only one minor chipping and three losses of retention were observed. Additionally, esthetics was excellent. Based on these results the clinical use of this kind of restoration is promising. (J Esthet Restor Dent 29:22-30, 2017)
First published: 29 September 2016
Gesehen am 17.09.2018